Performance and term structure of profit rate of sukuk bonds in Malaysia - Adesina-Uthman, Ganiyat Adejoke (2011)
Efficient functioning of financial system serves both as catalyst to deepen the domestic financial market and facilitates fair valuation of financial instruments. Financial institutions world-wide offer various financing solutions tailored to wide ranges of long and short term investment and financing needs. Bonds have been a key instrument in the financial system of developed and developing economies in meeting these needs. Sukuk or Islamic bonds surfaced in the Islamic Financial Market in the year 2000 to fulfill the needs of investors for long term investment financing that is Shariah compliant. Unlike conventional bonds that have an established infrastructure and yield-curve to forecast expected changes in yields and hence prices, the Sukuk lacks this facilities and have to rely on conventional yield curve for its pricing. This research fills this gap by constructing yield and credit curves based on a profit rate that is Shariah compliant to help both lenders and borrowers using Sukuk in making objective and religiously acceptable investment decisions. Hence, yield and credit curves for Government and corporate Sukuk as well as Spot and forward profit curves for government Sukuk were constructed using the one-factor CIR Model (1985) and Sukuk two-factor HJM model with no-arbitrage restrictions; that allows the term structure to vary with the profit rate; with time-dependent drift rate. Sukuk data was sourced for the period 2001 to 2009. The evidence from the two models showed that 89 percent of Malaysia Sukuk (Government and corporate) were not given a fair yield and therefore the bonds were mispriced. From the 89 percent that were mispriced, 44.4 percent were overpriced, 66.6 percent were underpriced. All the underpriced Sukuk were corporate Sukuk. It was observed that all the Government and corporate yield curves were humped. This is consistent with the Market Segmentation Hypothesis explanation for the curves. The non-monotonic yield curves indicates that there is uncertainty in the direction of the future spot profit rate. The upward slope of the curve implies in-built liquidity premium. The findings from OLS regression of spot and forward rates as well as inflation and forward rates showed that the forward profit rates had a very weak predictability power to forcast future spot profit rate and inflation. The findings on forward rate predictabilty to forecast future spot profit rates is not in support of the pure expectation hypothesis. The practice of benchmarking IFIs’ profit rate to available interest rate for better competition is therefore a distortion to true market value of underlying assets and hence,their returns was buttressed by the pricing pattern observed in the study, consistent with Muhammad Al-Bashir’s (2008) conclusions. A comparative analysis of Malaysian Government Sukuk and three different credit classes of corporate Sukuk; of which two are high investment grades and one low grade bonds showed that for the high gradethe corporate Sukuk performed better than the government Sukuk. The low grade Sukuk gave high yield relative to the GII benchmark rate. A comparison of yields of both government and corporate Sukuk with similar characteristics showed an upward sloping curve implying in-built liquidity premium to compensate investors for taking extra risk. In summary, the upward sloping profit yield curves of corporate and government Sukuk of different credit risk is consistent with the Liquidity Preference Theory (Biased Expectation Theory) and Market Segmentation Theory but inconsistent with the Pure Expectation hypothesis also known as Unbiased Expectation Theory. That is, the forward profit rates are not good predictor of future spot profit rates. Similar to the conventional bond market, the Sukuk market is dominated by risk-averse investors who require term premium to compensate for the risk involved in lending long. Thus the forward profit rate will exceed the forecasted spot rate by the liquidity or term premium and the forward rate will become a biased predictor of forecasted future spot rate. The predictability power of the forward rates to forecast future inflation was weak. These findings are similar to those reported by Gerlash (2003) for the conventional bond market in Hong Kong.